Comparative Analysis of the Subjective Picture of the World of Adult Men and Women - Ольга Семеновна Васильева; Надежда Михайловна Грачева (Rossijskij psihologičeskij žurnal., 2015)
The article is devoted to the study of subjective picture of the world of adult men and women. The main guideline to clarify qualitative features of representations of the self and the world we took four worldview models proposed by V. M. Smirnov: chaotic, antagonistic, mechanistic, organismic worldview models. We analyzed the difference in the severity of these worldview models by men and women. We investigated the relationship between the severity of a particular model of the world and the various aspects of the representations on the basis of the results of the test “Who am I?”, the scale methodology “The meaning of life orientation”, methodology “My World: 20 out of 80”, “Incomplete sentences”, “Scale of satisfaction” that identify different aspects of the relationship with the world, and significant others. In particular, we analyzed gender differences in terms of difficulty – easy way self-identification; the opposite trend of the world perception and its capabilities depending of the designation of gender identity at men and women; relationship representations of himself as a soul and the divine world order with the modalities of understanding of the world and its age features; the relationship of positive, neutral and negative characteristics of the world with the modalities of the worldview; communication of negative description of the world with the appropriate perception of other spheres of life; analyzed the effect of denial of the particular modality of the worldview. Due to the fact, that the most common modality of worldview is organismic modality is linked with the idea of self-representation as a spiritual nature, the article concludes about the meaning of this problem for the study not only at the level of a particular individual, but science in general.